Beginning to explore the experience of managing a direct payment for someone with dementia: The perspectives of suitable people and adult social care practitioners. (January 2016) - Laybourne, Anne H; Jepson, Marcus J; Williamson, Toby; Robotham, Dan; Cyhlarova, Eva; Williams, Val
Following legal improvements made around mental capacity together with the Health and Social Care Act, it is now possible for a direct payment to be paid to a 'Suitable Person' to manage on someone's behalf to purchase directly care and support services. People with dementia are a key group affected by this change in England of adult social care. We interviewed nine social care practitioners and seven Suitable People for people with dementia across five English local authorities to begin to examine their experiences of this new method of social care provision. Findings from thematic analyses suggest positive outcomes and multiple beneficiaries, but some challenges: potentially inappropriate processes, support planning, divergence in attitudes towards care and support outcomes. Implications for practice include obfuscation of recipients' and Suitable People's best interests and supporting practitioners to explore fully clients' aspirations for care and support.